THE EFFECT OF SERVICE QUALITY AND FACILITIES ON TOURIST SATISFACTION IN LEDOK SAMBI, REVIEWED FROM SPORT TOURISM - Pamungkas, Galih; Tyas, Widya Ghina; Humam, Muhammad Fatih; Sunaryo, Sunaryo (Universitas Negeri Yogyakarta, 2025)
This study aims to determine the effect of service quality on tourist satisfaction at Ledok Sambi tourist attraction, the effect of facilities on tourist satisfaction at Ledok Sambi tourist attraction, the effect of service quality and facilities simultaneously on tourist satisfaction at Ledok Sambi tourist attraction. This research method uses a quantitative descriptive method, data collection techniques with incidental sampling and instruments in the form of questionnaires. The data obtained were analyzed using descriptive analysis, hypothesis, multiple linear regression analysis, and determination coefficient, as well as validity and reliability tests to ensure the accuracy of the research instrument. The results of the study are as follows: (1) It is proven that service quality has an effect on tourist satisfaction, because the sig value is 0.000 <0.05 and the calculated t is 5.273> t table (0.197). (2) It is proven that facilities have an effect on tourist satisfaction, because the sig value is 0.000 <0.05 and the calculated t is 3.851> t table (0.197). (3) It is proven that the quality of service and facilities together have an effect on tourist satisfaction, because the sig value is 0.000 < 0.05 and the calculated f is 50.850 > F table (3.09). tourist satisfaction, because the sig value is 0.000 < 0.05 and the calculated f is 50.850 > F table (3.09). This finding strengthens the theory of tourist satisfaction which states that the quality of service and facilities are the main factors in forming a positive tourist experience.